2010
DOI: 10.1111/j.1540-8175.2010.01186.x
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Myxomas Grow Faster Than We Think

Abstract: The finding of a cardiac myxoma usually implies immediate consequent surgical excision to prevent embolic events. Reports with documented growth rate are therefore very rare, and the actual growth rate remains a controversial issue. We report the growth of a left atrial myxoma in an asymptomatic 65-year-old patient with several years of follow up for aortic valve disease. A MEDLINE search with the terms "cardiac myxoma and tumor growth" was performed. The calculated growth rate showed an average growth rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 22 publications
3
18
0
1
Order By: Relevance
“…Myxomas vary in size, but the growth rate is difficult to document because they are usually removed after diagnosis [69]. However, in our study, the one patient who underwent surgery 15 months after initial diagnosis showed a rapid growth rate of 0.41 cm/month.…”
Section: Discussionmentioning
confidence: 65%
“…Myxomas vary in size, but the growth rate is difficult to document because they are usually removed after diagnosis [69]. However, in our study, the one patient who underwent surgery 15 months after initial diagnosis showed a rapid growth rate of 0.41 cm/month.…”
Section: Discussionmentioning
confidence: 65%
“…As many as 4% of patients remain asymptomatic [4]. Atrial myxomas may grow quite rapidly, with a reported growth rates of average 0.49 cm/month [5]. Our patient had no detectable mass by CT only eight months earlier.…”
Section: Discussionmentioning
confidence: 59%
“…Our immunohistology data confirmed the expression of CD44 in myxoma. As a widely used cancer stem cell marker, CD44 expression indicates the malignant potential of cardiac myxoma [12]. It has been reported that myxomas are mainly composed of cellular elements including a variable number of blood cells [2] and amorphous myxoid matrix structures [13].…”
Section: Resultsmentioning
confidence: 99%